Toll-like receptor 4 is a master regulator for colorectal cancer growth under high-fat diet by programming cancer metabolism - Xianjing Hu; Sarwat Fatima; Minting Chen; Keyang Xu; Chunhua Huang; Rui-Hong Gong; Tao Su; Hoi Leong Xavier Wong; Zhaoxiang Bian; Hiu Yee Kwan (Cell Death and Disease, 2021)
Abstract Although high-fat diet (HFD) has been implicated in the development of colorectal cancer (CRC), the critical signaling molecule that mediates the cancer growth is not well-defined. Identifying the master regulator that controls CRC growth under HFD can facilitate the development of effective therapeutics for the cancer treatment. In this study, the global lipidomics and RNA sequencing data show that, in the tumor tissues of CRC-bearing mouse models, HFD not only increases tumor weight, but also the palmitic acid level and TLR4 expression, which are reduced when HFD is replaced by control diet. These concomitant changes suggest the roles of palmitic acid and TLR4 in CRC growth. Subsequent studies show that palmitic acid regulates TLR4 expression in PU.1-dependent manner. Knockdown of PU.1 or mutations of PU.1-binding site on TLR4 promoter abolish the palmitic acid-increased TLR4 expression. The role of palmitic acid/PU.1/TLR4 axis in CRC growth is further examined in cell model and animal models that are fed either HFD or palmitic acid-rich diet. More importantly, iTRAQ proteomics data show that knockdown of TLR4 changes the metabolic enzyme profiles in the tumor tissues, which completely abolish the HFD-enhanced ATP production and cancer growth. Our data clearly demonstrate that TLR4 is a master regulator for CRC growth under HFD by programming cancer metabolism.